2014
DOI: 10.1016/j.jvsv.2014.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Low-molecular-weight heparin modulates vein wall fibrotic response in a plasminogen activator inhibitor 1-dependent manner

Abstract: Background Treatment with low-molecular-weight heparin (LMWH) favorably alters the vein wall response to deep venous thrombosis (DVT), although the mechanisms remain unclear. Previous studies have suggested that LMWH alters the levels of circulating plasminogen activator inhibitor 1 (PAI-1), a known mediator of fibrosis, and may improve endogenous fibrinolysis. We hypothesized that LMWH favorably alters the vein wall response by binding of PAI-1 and acceleration of fibrinolysis. Methods Wild-type and PAI-1 −… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 42 publications
0
13
1
Order By: Relevance
“…A significant role of PAI‐1 in vascular thrombosis and thrombus resolution has been confirmed in both animal and human studies . Consistent with previous data suggesting that PAI‐1 gene deletion does not affect venous thrombogenesis, we found here that PAI‐1 overexpression failed to affect initial thrombus weight . However, the role of PAI‐1's ‘cofactor’ Vn remains understudied, with few animal studies evaluating thrombotic potential in Vn −/− mice and none specifically evaluating the deep venous system .…”
Section: Discussioncontrasting
confidence: 99%
“…A significant role of PAI‐1 in vascular thrombosis and thrombus resolution has been confirmed in both animal and human studies . Consistent with previous data suggesting that PAI‐1 gene deletion does not affect venous thrombogenesis, we found here that PAI‐1 overexpression failed to affect initial thrombus weight . However, the role of PAI‐1's ‘cofactor’ Vn remains understudied, with few animal studies evaluating thrombotic potential in Vn −/− mice and none specifically evaluating the deep venous system .…”
Section: Discussioncontrasting
confidence: 99%
“…lytic milieu (66). While we have previously shown that PAI-1 does not affect thrombus size at two days (67,68), it may be that in very early thrombosis, the VT size is affected by the fibrinolytic/antifibrinolytic balance as others have shown with decreased bleeding times in tumour-bearing mice exposed to low-dose LPS (58).…”
Section: What Does This Paper Add?mentioning
confidence: 61%
“…Furthermore, most studies have required pre-treatment or peri-DVT initiation of treatment to demonstrate a therapeutic anticoagulant effect. We did not observe an additive benefit of combining both therapies in established murine stasis DVT, possibly related to the relative resistance of murine DVT to enoxaparin, and/or to heightened sensitivity of murine DVT to statins, and/or possible fundamental limits to thrombus reductions that are achievable in the murine stasis IVC model [ 61 ].…”
Section: Discussionmentioning
confidence: 99%